PERANCANGAN DESAIN KEMASAN PRODUK MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) STUDI KASUS PADA PT. XYZ - Dwi Rahayu Syawal Indah; Ayudyah Eka Apsari (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Competition in the household product industry encourages the development of packaging designs that not only protect the product but also influence consumer comfort and perception. This study analyzes consumer perceptions of liquid soap packaging and develops an improved design using the Quality Function Deployment (QFD) method. The research focuses on the liquid soap packaging of PT Anugrah Multi Ragam Indonesia, with data collected from 20 consumers in Yogyakarta through questionnaires, observations, and interviews. The data were tested for validity and reliability and analyzed using the House of Quality (HoQ). The results show that functional aspects, particularly ease of use, structural strength, and durability, are the main consumer priorities. The QFD analysis identifies packaging dimensions and shape, as well as material type, as key technical priorities, with a recommended capacity of 500–750 ml using PET or HDPE materials